Nova metodologia para calibração de sistemas de localização de descargas atmosféricas - Claudia Rejane de Mesquita (2006)
Lightning Location Systems (LLSs) are advanced tools to provide data related to lightning occurrence. They employ remote measurements of electromagnetic field that is irradiated by lightning current to provide relevant information for lightning protection application. As any physical system, the LLSs are submitted to errors in their indications. Such errors may result from the hypothesis assumed on system conception and mainly from the influence of environment factors on the propagation of electromagnetic signal before it is detected at the system remote stations. The manufacturer tries to compensate the system errors by means of corrections and adjustments, which are implemented at LLS from statistical analysis of their indications and redundancy. Nevertheless, eventual systematic errors, such as those ones associated to the influence of relief and soil conductivity, may be not corrected by such compensation. In this work an innovative methodology able to allow an effective calibration of LLS was developed. Its approach is based on the collection of reference data related to actual lightning events to be compared to LLS registers. In order to generate such references, a special electronic device was developed. It is able to register the instant of lightning occurrence and the current waveform, by means of non-direct measurement of the magnetic field associated to the lightning current. Using data from the LLS installed in Minas Gerais State, the geographic distribution of such electronic devices was designed to compose a local network intended to calibrate this system. As a first step, a parcel of the network was installed, placing the devices at sites of recognized high density, in order to collect a significant amount of data in a short period of time.